2015
DOI: 10.1080/01446193.2015.1021703
|View full text |Cite
|
Sign up to set email alerts
|

Project organizing as a problem in information

Abstract: One of the most influential perspectives in business and management has been the Carnegie School, represented by such luminaries as James March, Hebert Simon, Oliver Williamson and Zur Shapira. The perspective underpins much of contemporary organization theory and organizational economics. Yet there have only been limited attempts to apply it to the domain of construction economics and management. An important exception to this statement is the application of Williamson's transaction cost economics to the gove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 63 publications
0
15
0
Order By: Relevance
“…Extant literature has found that particularly strong personal ties between people in different parts of a large organization expand the chances of successful adoption and implementation of new ideas (Kijkuit & van den Ende, 2010). Although the temporary nature of projects might not allow sufficient time for establishing such ties, the experience of Crossrail shows that managers can effectively create the conditions for communicating and sharing ideas, and use information systems to foster innovation (Winch, 2010;Winch, 2015) and enhance "network connectivity" (Björk & Magnusson, 2009) organization, and task assignment) but also the definition of methods and rules of communication (Phillips, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…Extant literature has found that particularly strong personal ties between people in different parts of a large organization expand the chances of successful adoption and implementation of new ideas (Kijkuit & van den Ende, 2010). Although the temporary nature of projects might not allow sufficient time for establishing such ties, the experience of Crossrail shows that managers can effectively create the conditions for communicating and sharing ideas, and use information systems to foster innovation (Winch, 2010;Winch, 2015) and enhance "network connectivity" (Björk & Magnusson, 2009) organization, and task assignment) but also the definition of methods and rules of communication (Phillips, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…While a project's life cycle can take on a number of forms (e.g. Lindkvist et, al., 1998), a governance structure that follows the traditional project life cycle model is expected to be able to process information to reduce uncertainty (Winch, 2015) and to monitor the progression of work through what are termed stage gates, which have become a common feature in the project management systems of large infrastructure clients. It is at these stage gates where progress against predefined project or individual stage goals can be assessed before gaining approval (i.e.…”
Section: The Life Cycle Modelmentioning
confidence: 99%
“…This process of bracketing practices to identify and develop the abstract event sequence and their boundaries, while seemingly occurring sequentially, enabled me to identify the generative mechanisms involved in re-creating patterns of action and the processual nature of the model, which are discussed in the following section. (Söderlund, 2012;Morris, 2013), commonly structured through sequential stages to process information (Winch, 2015) and monitor the progression of work through stage gates and representing time as linear by fixing a predefined date when the organisation will be terminated (Lundin and Söderholm, 1995;Bakker et. al., 2016).…”
Section: Table 2 -Abstract Event Sequence and Activities For Each Roumentioning
confidence: 99%
“…Differences include the scope of information available to the public, how and over what time frame the public is engaged, and what the public may hope to influence. Of particular importance here is that urban development projects are inherently a “problem in information” (Winch, 2015), where the degree of certainty increases as the project progresses. Aligning the public engagement with the project life cycle is, therefore, problematic, and public engagement events become a series of, more or less, one-off project milestone events.…”
Section: Background and Contextmentioning
confidence: 99%